Comparison Analysis Of Optimal Portfolio Formation Results Using Single Index Model With Markowitz Model During The Covid 19 Pandemic In LQ 45 Index Company - Elly Susanti; Nelly Ervina; Ernest Grace; Liper Siregar (International Journal of Educational Research & Social Sciences, 2021)
Investors with a conservative type have a tendency to avoid risk (avoid risk) can invest their funds. Therefore, a diversification is needed to determine the optimal stock portfolio, including the Markowitz model and the Single Index Model. This study aims to find out the comparison of optimal portfolio formation results by using markowitz model and single index model in the covid 19 pandemic as the object of research there are companies listed in LQ Index 45. For the period used is for 3 periods, namely February 2020 to July 2021. For data processing using the Microsoft Excel application program. The results of the expectations of return and risk from the Markowitz model and single index model show that the portfolio that is better used is the markowitz model because it has a higher return than the single index model.